Australian Software Engineering Conference (ASWEC'06) 2006
DOI: 10.1109/aswec.2006.36
|View full text |Cite
|
Sign up to set email alerts
|

Model-based runtime analysis of distributed reactive systems

Abstract: As interactions and dependencies within distributed reactive systems increase, the problem of detecting failures which depend on the exact situation and environmental conditions they occur in grows. As a result, not only the detection of failures is increasingly difficult, but also the differentiation between the symptoms of a fault, and the actual fault itself, i. e., the cause of a failure. This thesis proposes an efficient approach for the analysis of distributed reactive systems at runtime. It introduces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 136 publications
0
28
0
Order By: Relevance
“…Recent work has shown that the presence of a status message can sometimes be used to overcome controllability problems, in testing from a DFSM, if suitable test sequences are chosen [20]. It might be possible to implement something similar to a status message using monitors, which have been developed for monitoring and debugging distributed systems [3,18,41,58].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that the presence of a status message can sometimes be used to overcome controllability problems, in testing from a DFSM, if suitable test sequences are chosen [20]. It might be possible to implement something similar to a status message using monitors, which have been developed for monitoring and debugging distributed systems [3,18,41,58].…”
Section: Related Workmentioning
confidence: 99%
“…Let us note that if t is the null process ⊥, which cannot send any input, then t p =⊥ p 3. We are only interested in the traces defined by a local tester since each tester only observes a local trace.…”
mentioning
confidence: 99%
“…In addition, there are approaches in which the testers communicate in order to determine the global trace that occurred (see, for example, [25], [26]). There has also been a significant amount of work on monitoring, in which we wish to determine the global state of the SUT (see, for example, [27], [28], [29], [30], [31]). In contrast to these, we are concerned with black-box testing and we are interested in conformance relations that capture the observational power of potential users.…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive prior work on runtime monitoring for assurance and for error detection and recovery (e.g., 22,23 ). The main novelty in the approach proposed here is use of a safety case as the source of monitored properties.…”
Section: Further Prospectsmentioning
confidence: 99%